Omega-3 PUFA ameliorates hyperhomocysteinemiainduced hepatic steatosis in mice by inhibiting hepatic ceramide synthesis - DONG Yong-qiang; ZHANG Xing-zhong; SUN Lu-lu; ZHANG Song-yang; LIU Bo; LIU Hui-ying; WANG Xian; JIANG Chang-tao (Acta Pharmacologica Sinica, 2017)
Abstract Hyperhomocysteinemia (HHcy) is a key risk factor in hepatic steatosis. In this study, we applied a metabolomic approach to investigate the changes in the metabolite profile due to HHcy-induced hepatic steatosis and the effects of omega-3 PUFA (polyunsaturated fatty acid) supplementation in mice. HHcy was induced in mice by giving DL-Hcy (1.8 g/L) in drinking water for 6 weeks, then the mice were sacrificed, and the metabolic profiles of the liver and plasma were analyzed through UPLC-ESI-QTOFMS-based lipidomics. Hepatic triglycerides and cholesterol were further assayed. The expression of ceramide metabolism-related genes was measured by quantitative PCR. Compared with control mice, HHcy mice exhibited hepatic steatosis with a notable increase in ceramide-related metabolites and subsequent upregulation of ceramide synthesis genes such as Sptlc3, Degs2, Cer4 and Smpd4. Omega-3 PUFA was simultaneously administered in HHcy mice through chow diet containing 3.3% omega-3 PUFA supplement for 6 weeks, which significantly ameliorated Hcy-induced hepatic steatosis. The decrease in hepatic lipid accumulation was mainly due to reduced hepatic levels of ceramides, which was partly the result of the lower expression of ceramide synthesis genes, Sptlc3 and Degs2. Similar beneficial effects of DHA were observed in Hcy-stimulated primary hepatocytes in vitro. In summary, Hcy-induced ceramide elevation in hepatocytes might contribute to the development of hepatic steatosis. Furthermore, downregulation of ceramide levels through omega-3 PUFA supplementation ameliorates hepatic lipid accumulation. Thus, ceramide is a potential therapeutic target for the treatment of hepatic steatosis